Mechanistic basis for LQT1 caused by S3 mutations in the KCNQ1 subunit of I(Ks) - Eldstrom, Jodene (The Rockefeller University Press, 2010)
Long QT interval syndrome (LQTS) type 1 (LQT1) has been reported to arise from mutations in the S3 domain of KCNQ1, but none of the seven S3 mutations in the literature have been characterized with respect to trafficking or biophysical deficiencies. Surface channel expression was studied using a proteinase K assay for KCNQ1 D202H/N, I204F/M, V205M, S209F, and V215M coexpressed with KCNE1 in mammalian cells. In each case, the majority of synthesized channel was found at the surface, but mutant I(Ks) current density at +100 mV was reduced significantly for S209F, which showed ∼75% reduction over wild type (WT). All mutants except S209F showed positively shifted V(1/2)’s of activation and slowed channel activation compared with WT (V(1/2) = +17.7 ± 2.4 mV and τ(activation) of 729 ms at +20 mV; n = 18). Deactivation was also accelerated in all mutants versus WT (126 ± 8 ms at −50 mV; n = 27), and these changes led to marked loss of repolarizing currents during action potential clamps at 2 and 4 Hz, except again S209F. KCNQ1 models localize these naturally occurring S3 mutants to the surface of the helices facing the other voltage sensor transmembrane domains and highlight inter-residue interactions involved in activation gating. V207M, currently classified as a polymorphism and facing lipid in the model, was indistinguishable from WT I(Ks). We conclude that S3 mutants of KCNQ1 cause LQTS predominantly through biophysical effects on the gating of I(Ks), but some mutants also show protein stability/trafficking defects, which explains why the kinetic gain-of-function mutation S209F causes LQT1.